Spatiotemporal variation of phosphorus use efficiency across 70 lakes in China: Implications for lake eutrophication management. (September 2022) - Liu, Haixia; Liu, Qingqing; Zhao, Jian; Zhang, Xiaoyu; Ding, Lin; Liu, Yue; Fu, Guo
Highlights: Phosphorus use efficiency varied widely across 70 lakes in China. Lakes in the Yungui Plateau region were more susceptible to phosphorus pollution. Temperature accounted for seasonal variations in the phosphorus use efficiency. Lake sensitivity to phosphorus pollution increased over time in 30% of lakes studied. ETP is a better indicator than TP to reflect the actual growth of algae. Abstract: Reducing phosphorus input is currently the main lake eutrophication management strategy, but algal blooms persist in many lakes despite effective phosphorus abatement measures. This study analyzed monitoring data across 70 Chinese lakes using statistical methods to reveal the spatiotemporal characteristics of the algae production efficiency of total phosphorus (ETP) and the driving factors of ETP changes. The results showed that ETP ranged from 0.01 to 1.87 across 70 Chinese lakes from 2016 to 2018. Spatially, lakes with higher ETP values were concentrated in the Yungui Plateau region due to its natural conditions, which were suitable for phytoplankton growth. Temporally, the ETP values from July to October were higher than in other months. In addition, over 30% of lakes exhibited rising ETP values, and these were mainly located in the Eastern Plain region. These spatiotemporal differences reveal the reason for the failure of phosphorus control based on a universal regression equation in eutrophication management for some individual lakes. Nitrogen-limited or co-limited lakes were also found mainly located in the Northeast Plain region, and it was confirmed that alkalinity was the main factor affecting algae growth in the Qingzang Plateau region. Our results indicate that TP reduction alone, based on the empirical relationship between chlorophyll-a and TP, is insufficient to accurately control eutrophication at the lake-specific scale, and individualized lake management strategies considering the variations in ETP are recommended.